The Animal Girl : Two Novellas and Three Stories - Fulton, John, 1967- (Book collections on Project MUSE., 2007)
The five heartbreaking and radiant stories in John Fulton's The Animal Girl explore the awkwardness of situations in which grief and erotic love collide. Here are people in extremis, struggling mightily, and often failing, to keep it together. In the Pushcart Prize-winning?Hunters,? Fulton contrasts the humorous clumsiness of dating with the grim realities of death in the tale of a middle-aged woman who keeps her cancer a secret when she starts a relationship with an avid hunter. In the novella-length title story, a lonely adolescent girl deals with the recent loss of her mother and the alie.